O gênero discursivo convite de casamento: configuração e proposta didática para aulas de língua portuguesa - Mendes, Paula Marina (2022)
This research seeks to analyze the dimensions of the wedding invitation from the Bakhtinian perspective of discourse genres and to propose its didacization for high school Portuguese classes. By presenting its own contexts of production, circulation, and reception, interlocutors involved in their ideological positions, unique thematic content, defined compositional structure, and peculiar linguistic-enunciative marks, the wedding invitation brings great possibilities for study in the area of dialogical language studies. The research is anchored on three theoretical axes: i) the Bakhtin Circle axis (BAKHTIN, 2010; 2013; 2016; VOLOCHÍNOV, 2013; VOLÓCHINOV, 2018), of philosophical-linguistic basis, for the study of concrete utterances belonging to the discursive genre wedding invitation; ii) the axis of studies on the historical context of marriage, taking into account the wedding ceremony as a socio-historical-discursive event, by Del Priore (2007; 2011), Engels (2012), Gandra (1983), and Prost and Vincent (1992); and iii) the didactic axis, grounded in Critical-Historical Pedagogy (SAVIANI, 1991; 2013; 2019) and in specific didactic proposal for genres of discourse, by Lunardelli (2021). From the three axes, we investigate: i) What would the extraverbal and verbal-visual dimensions of the wedding invitation look like, in the light of the Bakhtinian perspective of discourse genres? ii) In what ways can Brazilian dialogical language studies, aligned to Critical-Historical Pedagogy, propose didactic paths to teaching the discursive genre wedding invitation for high school Portuguese classes? As a general objective, the research aims to investigate the configuration of the discourse genre of wedding invitations from the perspective of Bakhtin's Circle and to propose didactic-methodological directions for the teaching of the genre. As specific objectives, they are listed: i) discuss the concepts related to the scope of genre of discourse from the perspective of Bakhtin's Circle and Brazilian dialogical studies of language; ii) historically and socially contextualize marriage as a ceremony/event; iii) identify the extraverbal and verbal-verbal dimensions of utterances of the discursive genre wedding invitation; and iv) propose didactic paths for the teaching of the discourse genre wedding invitation in high school Portuguese classes. This theoretical research is characterized by being of a social nature, belonging to Applied Linguistics, of qualitative approach, with documentary analysis by sampling. The data generation is configured from the wedding invitations given by the families, by means of the Free and Informed Consent Form. Regarding the analysis of the wedding invitations, it is considered that there are significant changes in affective relationships in society, transformations and family building processes: from a society with more conservative values to a more creative and open society for new loves. Working with this discourse genre in high school Portuguese classes is relevant, in order for teachers to reflect with their students about the various ways of teaching and learning the Portuguese language, allied to expanding the repertoire of discourse genres as teaching-learning objects. Finally, the research contributes to the insertion of the discourse genre wedding invitation in Portuguese language classes, promoting reflection on a given social/ideological positioning of man in his world, in this case, the relationship of human beings with marriage.